Gestão de estoques e marketing: um estudo de correlação em uma empresa do ramo de cosméticos localizada na cidade de São Paulo do Potengi/RN - Câmara Neto Segundo, Joel da Costa (Universidade Federal Rural do Semi-Árido, 2019)
Faced with the high level of demand of commerce, many people use the possibility of having their own business as a financial alternative and perhaps to have a successful venture. In many cases, small entrepreneurs face difficulties in their business due to some information deficiencies about their own company, which makes it difficult to plan and implement competitive and marketing strategies. This paper aims to show the owner of the company Paulinha Cosmeticos where to direct their strategies towards their products in stock. Thus, a methodology of visits to the company's physical space was used to observe the business progress, possible problems and suggestions for improvement. The case study was aided by an ABC analysis, which provided all information about the company's inventory, which products give the highest financial return, suggestions for giving greater inventory turnover and which products should be explored in promotions. In its stock, Paulinha Cosmeticos company owns 23.08% of its products, corresponding to 59.17% of the total value of its merchandise. Relating the ABC analysis data to marketing, it can be concluded that the company has great potential to grow, but needs a new market posture, seeking to improve the company's image, reach more customers and update itself in the new media of communication.
Monografia
Keywords: Cosméticos; Marketing; Análise ABC; Estoque; Empresa; Cosmetics; Marketing; ABC analysis; Stock; Company; ENGENHARIAS::ENGENHARIA DE PRODUCAO